The Ultimately Determinant Role of Economy in Yilmaz Güney's Movies: An Essay From the Perspective of Marxist Theory - Betül Sarı Aksakal (CINEJ Cinema Journal)
The study examines a different aspect of the films of actor, screenwriter, and director Yılmaz Güney, who brought a new sense of reality to Turkish cinema. Güney's film Umut (The Hope), which he acted and directed in 1970, is a turning point for Yılmaz Güney cinema and Turkish cinema. The breath of Marxism can be felt in almost all of Yılmaz Güney's films after The Hope. In his films, Güney aimed to convey to the audience the fundamental contradictions of Turkish capitalism, the socioeconomic inequalities it created, and the resulting class differences. It can be argued that Güney's films discussed within the scope of the study Umut, 1970 (The Hope), Endişe, 1974 (The Anxiety), Sürü, 1978 (The Herd), Düşman, 1979 (The Enemy) focus on social class differences in the capitalist system by relying on Marxist ideology. Although the reasons for these differences in the movies are associated with factors such as politics, ideology, religion, culture, family, and education, it is thought that the most significant share of the factors that play a role in the formation of social classes is given to the economy. The study started with the problem of proving this claim. The films discussed within the study's scope revealed that the economy is the critical factor determining social class differences.